Vegetative Growth of Kale Land (Ipomoea reptans poir.) Due to Different doses of NPK and Bokashi Fertilizer - Ahmad Raksun; Mahrus Mahrus; I Gde Mertha (Universitas Mataram, 2020)
In order to maintain soil fertility, NPK fertilizer applications that have been carried out by farmer need to be combined with non chemical fertilizer such as bokashi. Research on vegetative growth of kale land due to NPK and bokashi fertilizer has been carried out in Bajur Village, West Lombok Regency. The purpose of this research was to detemine: (1) vegetative growth of kale land due to different doses of NPK fertilizer, (2) vegetative growth of kale land due to different doses of bokashi, (3) the effect of interaction of NPK and bokashi fertilizer on growth of kale land, (4) Optimum dose of NPK fertilizer and bokashi for kale land. This research used 2 factors design. The first factor is the dose of NPK fertilizer and the second factors is the dose of bokashi. The growth parameters measured were stem height, leaf length, leaf width and number of kale land leaf. Reseach data analyzed using analysis of variance. The results showed that: (1) NPK fertilizer treatment significantly affected stem height, leaf length and kale leaf width, but have no significant effect on the number of kale land leaves, (2) bokashi aplication significantly affected stem heght, leaf length and kale land leaf width but did not significantly affect the number of kale land leaves, (3) the interaction of NPK fertilizer and bokashi did not significantly affect all growth parameters measured, (4) the optimun dose of bokashi for kale land is 1,2 kg for 8 kg of soil and the optimum dose of NPK fertilizer is 1,5 g per plant.ÃÂ It is recommended that kale land famers use 1,2 kg bokashi for 8 kg of soil and 1,5 g NPK fertilizer per plant.